Lifestyle habits of Croatian diabetic population : observations from the Croatian adult health survey - Magaš, Saša (Array, 2009)
Summary: The aim of this study was to assess the behavioural risk factors in Croatian diabetic population and to compare them with the lifestyle habits of individuals with no known history of diabetes. The study was a part of the Croatian Adult Health Survey (CAHS), a cross-sectional survey that provided comprehensive health assessment of the Croatian adult population. Risk factors were defined as an unhealthy nutritional regimen, excessive alcohol consumption, smoking and lack of physical activity. Physical inactivity was the most prevalent risk factor observed in a significant number of both diabetic and non-diabetic subjects (44.8% and 29.1%). It was also the only behavioural risk factor that was more prevalent in the diabetic individuals as compared to those without diabetes. Alcohol consumption did not vary significantly between the two groups (5.8% vs. 6.3%), while unhealthy dietary pattern and smoking were less frequent in respondents with diabetes (10.0% vs. 16.5% and 14.3% vs. 23.2%, respectively). Among diabetic patients, a significantly larger proportion of men than women reported smoking (19.2% vs. 10.0%), whereas no such sex-related differences were observed in other behavioural risk factors. Although the most prominent risk factor in diabetic patients was physical inactivity, a significant proportion of respondents with diabetes also reported the presence of other risk factors investigated in this survey. Since the majority of diabetic patients do not reach their treatment goals, there is a substantial need for curative and preventive interventions. Given the importance of physical activity in the treatment and prevention of diabetes and the high proportion of inactive diabetic patients, any future preventive programme in Croatia should address that risk as well